Surface modification of gold nanoparticles and nanoclusters - Sokolowska, Karolina (2016)
Gold nanoparticles are used in many beneficial technological applications in biochemistry, medicine and electronics. Among them, monolayer protected gold nanoclusters (MPCs) have received a significant attention in the scientific community due to their well-defined atomic structure, which is important for fundamental studies of nanoparticles properties and their functionalization. These particles, with a precise number of atoms, exhibit size-dependent optical, chemical and electronic properties. The thesis focuses on the structure, preparation, characterization, and properties of MPCs. For multifunctional applications, gold nanoparticles are an ideal class of compounds for surface functionalization reactions. Incorporating various active groups into nanoparticles’ surface opens new possibilities for broad applicability. The second part of this thesis describes surface modification methods of gold nanoparticles and MPCs. Typical surface modification methods are ligand exchange, chemical conjugation, physical conjugation, and bioconjugation.